2020
DOI: 10.5851/kosfa.2019.e82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Bioactive Peptides on Antioxidant Potential of Broiler Breast Meat and Physicochemical Characteristics of Nuggets

Abstract: Poultry meat is generally exposed to quality deterioration due to lipid oxidation during storage. Oxidative stability of meat can be increased by feed supplementation. Aim of the current study was to investigate the effect of dietary supplementation of fish waste derived bioactive peptides on antioxidant potential of broiler breast meat and physico-chemical characteristics and quality parameters of nuggets prepared from breast meat. 180 broiler birds (six groups of 30 birds) were purchased. Each group was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The findings suggested that dietary supplementation of bioactive peptides obtained from fish waste helped in increasing the antioxidant potential and shelf stability of broiler meat when they were stored even under frozen conditions. This study also concluded that natural bioactive peptides in the form of dietary nutraceuticals can be a suitable substitute to the commercial chemical anti-oxidants used in poultry feeding to keep the quality of meat and by-products such as nuggets (Aslam et al 2020). In another experiment, researchers used diets supplemented with linseed oil, echium oil, fish oil and/or algal biomass to study their health promoting effects on various parameters of immune response including total lipid profile, lymphocyte proliferative effects and NK cell activity among thymocytes and splenocytes in one day A c c e p t e d M a n u s c r i p t old male broiler chickens.…”
Section: Designer and Functional Foods Conceptsmentioning
confidence: 74%
“…The findings suggested that dietary supplementation of bioactive peptides obtained from fish waste helped in increasing the antioxidant potential and shelf stability of broiler meat when they were stored even under frozen conditions. This study also concluded that natural bioactive peptides in the form of dietary nutraceuticals can be a suitable substitute to the commercial chemical anti-oxidants used in poultry feeding to keep the quality of meat and by-products such as nuggets (Aslam et al 2020). In another experiment, researchers used diets supplemented with linseed oil, echium oil, fish oil and/or algal biomass to study their health promoting effects on various parameters of immune response including total lipid profile, lymphocyte proliferative effects and NK cell activity among thymocytes and splenocytes in one day A c c e p t e d M a n u s c r i p t old male broiler chickens.…”
Section: Designer and Functional Foods Conceptsmentioning
confidence: 74%
“…The formation of hydroperoxides and aldehydes are indicators of lipid oxidation [ 88 ]. Piñuel, et al [ 89 ] found the addition of phaseolin isolated from red kidney bean to zebrafish inhibited the lipid oxidation by 82%, and Aslam, et al [ 90 ] found that the addition of fish protein hydrolysate to chicken meat breast during storage delayed the lipid oxidation and all unwanted changes.…”
Section: Resultsmentioning
confidence: 99%
“…Predicted This analysis of degree of hydrolysis (DH) was conducted by following the procedure (Adler-Nissen 1979;Aslam et al, 2020). A hydrolyzed 125 mg sample was added in 25 mL of 1% SDS solution.…”
Section: Enzymatic Hydrolysis Of Fish Proteinsmentioning
confidence: 99%